2017
DOI: 10.1111/mmi.13728
|View full text |Cite
|
Sign up to set email alerts
|

The Bacillus subtilis germinant receptor GerA triggers premature germination in response to morphological defects during sporulation

Abstract: During sporulation in Bacillus subtilis, germinant receptors assemble in the inner membrane of the developing spore. In response to specific nutrients these receptors trigger germination and outgrowth. In a transposon-sequencing screen, we serendipitously discovered that loss of function mutations in the gerA receptor partially suppress the phenotypes of >25 sporulation mutants. Most of these mutants have modest defects in the assembly of the spore protective layers that are exacerbated in the presence of a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 50 publications
6
33
0
Order By: Relevance
“…As expected, the deletion of gerA gene eliminates the change of phase brightness with forespores (Figure 3A; lower panel, Figure 3B, and Movie 5). This observation appeared complementary to the genetic analyses of a recent paper (18). This study by Ramirez-Guadiana et al elegantly demonstrated that GerA-mediated premature germination can act as a quality-control system of forespore morphogenesis; i.e .…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…As expected, the deletion of gerA gene eliminates the change of phase brightness with forespores (Figure 3A; lower panel, Figure 3B, and Movie 5). This observation appeared complementary to the genetic analyses of a recent paper (18). This study by Ramirez-Guadiana et al elegantly demonstrated that GerA-mediated premature germination can act as a quality-control system of forespore morphogenesis; i.e .…”
Section: Resultssupporting
confidence: 71%
“…While a previous study suggested that the frequency of premature germination may be constant in different media (18), our model predicted that environmental conditions, that affect the membrane potential, should alter the frequency of premature germination. To this end, we focused on glutamate availability because glutamate is a gating molecule for the B. subtilis potassium channels which remain closed in glutamate rich media (2, 4).…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations